2020
DOI: 10.1002/rco2.18
|View full text |Cite
|
Sign up to set email alerts
|

Cancer‐induced cardiac atrophy adversely affects myocardial redox state and mitochondrial oxidative characteristics

Abstract: Background Cachexia presents in 80% of advanced cancer patients; however, cardiac atrophy in cachectic patients receives little attention. This cardiomyopathy contributes to increased occurrence of adverse cardiac events compared with age‐matched population norms. Research on cardiac atrophy has focused on remodelling; however, alterations in metabolic properties may be a primary contributor. The purpose of the study is to determine how cancer‐induced cardiac atrophy alters mitochondrial turnover, mitochondria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 85 publications
2
23
0
Order By: Relevance
“…Increased inflammatory signaling leading to proteolytic degradation of sarcomeric proteins 11 , 14 and upregulated autophagy 15 have been proposed as potential mechanisms underlying ventricular atrophy. Fetal gene reactivation 14 , mitochondrial morphological 11 and functional changes 16 , 17 , and aberrant fatty acid oxidation 18 may contribute to both decreased cardiac mass and function, although more work is needed to understand causal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Increased inflammatory signaling leading to proteolytic degradation of sarcomeric proteins 11 , 14 and upregulated autophagy 15 have been proposed as potential mechanisms underlying ventricular atrophy. Fetal gene reactivation 14 , mitochondrial morphological 11 and functional changes 16 , 17 , and aberrant fatty acid oxidation 18 may contribute to both decreased cardiac mass and function, although more work is needed to understand causal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Muscle loss correlates to tumor burden and is due to an increase in protein‐degradation rate, mainly through ATP‐dependent proteolysis, 34,96 without change in protein synthesis rate. This leads to a decline in muscle and about 5% loss in bone density, 34 as well as cardiac atrophy 97 . Recent studies have revealed alterations of diaphragm function, hepatic metabolism, and the gut microbiome in LLC cachexia.…”
Section: Preclinical Modeling Of Cancer Cachexiamentioning
confidence: 99%
“…This leads to a decline in muscle and about 5% loss in bone density, 34 as well as cardiac atrophy. 97 Recent studies have revealed alterations of diaphragm function, hepatic metabolism, and the gut microbiome in LLC cachexia. This model has revealed important roles for host-derived initiators of cachexia as well as potential therapeutics, in part because of its compatibility with C57BL/6 strains of genetically modified mice.…”
Section: Lewis Lung Carcinomamentioning
confidence: 99%
“… 142 Our recent evidence indicates that cardiac tissue from LLC-induced tumor-bearing mice and in vitro models of cardiac cachexia exhibit elevated mitochondria content (likely driven by reduced mitophagy suggesting accumulation of damaged mitochondria), decreased mitochondrial mRNA translation rate, and increased mitochondrial ROS emission with reduced scavenging capacity. 143 Unfortunately, to date cardiac cachexia remains significantly understudied. Therefore, there remains a critical need to identify key underlying mechanisms in development of cardiac cachexia.…”
Section: Alterations To Non-skeletal Muscle Tissues During Development and Progression Of CCmentioning
confidence: 99%